2016
DOI: 10.20533/licej.2040.2589.2016.0307
|View full text |Cite
|
Sign up to set email alerts
|

Improving Literacy Instructional Practices in Primary Schools in Nigeria: Strategies that Work

Abstract: Poor teaching methods are blamed for a large number of Nigerian pupils in government schools becoming either non-readers or struggling readers [20]. This study investigated the effects of a Reading Intervention that trained primary school teachers in specific strategies of teaching reading skills in order to enhance instructional practices. In a quasiexperimental design with 15 teachers and 140 primary pupils, teachers were trained for four weeks using activities derived from the whole language or literature-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This implies that despite the interventions being carried out made a difference in reading performance of the learners. These results concur with those of Oyetunde et al, (2016) whose study on strategies that work on improving literacy instructional practices in primary schools in Nigeria revealed that the treatment group significantly outperformed the control group on all nine reading skills sub-tests.…”
Section: Results From the Reading Test Experimentssupporting
confidence: 89%
“…This implies that despite the interventions being carried out made a difference in reading performance of the learners. These results concur with those of Oyetunde et al, (2016) whose study on strategies that work on improving literacy instructional practices in primary schools in Nigeria revealed that the treatment group significantly outperformed the control group on all nine reading skills sub-tests.…”
Section: Results From the Reading Test Experimentssupporting
confidence: 89%
“…Nigerian teachers have been found to lack the pedagogical knowledge and skills required to teach early reading skills effectively [31,45,46], with recent evidence from five states in northern Nigeria finding that 91% of Grade 3 children score zero on English (L2) and Hausa (L1) reading comprehension assessments [47]. Similar trends are observed in other northern states where early grade reading skills are not being mastered in local languages.…”
Section: School Policy In Nigeriamentioning
confidence: 89%
“…Estimates suggest that children in rural areas account for 63% of this total, and 84% of this amount are from the lowest income quartile [30]. Ineffective teacher training programmes [31], underfunded school infrastructure [32] and over-populated classrooms [33][34][35] are cited as contributing to Nigeria's learning crisis [36].…”
Section: School Policy In Nigeriamentioning
confidence: 99%
“…Poor reading outcomes may be attributed to the ineffective implementation of the reading component of the English language curriculum (Yusuf, 2014). Some of the factors hypothesised to be related to the poor implementation of the reading curriculum are inadequate preparation of teachers (Oyetunde et al, 2016; Barnes et al, 2019), teachers' lack of necessary skills or instructional techniques to teach reading (Oyetunde et al, 2016; Enighe and Afangideh, 2018), children's poor reading habits (Enighe and Afangideh, 2018) and inadequate provision of TLM (Ekpo et al, 2007; Tuimur and Chemwei, 2015; Abu‐Ubaida et al, 2017; Bukoye, 2019).…”
Section: Background and Contextmentioning
confidence: 99%